STATISTICAL STUDY REGARDING THE PREVALENCE OF THE PERIODONTAL PATHOLOGY ON THE TEENAGER PATIENT - Oana Potârnichie; Sorina Solomon; Liliana Păsărin; Alexandra Mârțu; Irina Ursărescu; Diana Cristala Niţescu; Silvia Mârțu (Romanian Society of Oral Rehabilitation, 2013)
Introduction: Periodontal disease can manifest different forms on children and teenagers, with a large number of lesions, from gingival tissue destruction to profound periodontal lesions which can lead even to tooth loss in certain cases. Purpose of the study: The purpose of this study was to assess the presence or the severity of the periodontal disease and the oral hygiene in a group of teenagers. Materials and methods: The study group consisted in a number of 33 teenagers. We realized: clinical examination on each patient, with bleeding index, gingival and periodontal inflammation index and questionnaires, with general patient data, chief complaints, periodontal history, risk factors, sanitary education degree. Results: Most cases presented chronic gingivitis determined by bacterial plaque; only a few number of patients presented alveolar bone loss. In these cases class I Miller recessions were predominant. Discussions: Practically, all the oral manifestations included bacterial plaque accumulations and a intensification of the microbiota, creating favorable conditions for gingival inflammations. Conclusions: Every patient presented a certain degree of periodontal impairment. An educational program leading to a decrease in frequency of the periodontal disease is necessary.